Long-Term Risk Factors for Intracranial In-Stent Restenosis From a Multicenter Trial of Stenting for Symptomatic Intracranial Artery Stenosis Registry in China - Guo, Xu; Ma, Ning; Gao, Feng; Mo, Da-Peng; Luo, Gang; Miao, Zhong-Rong (Frontiers in Neurology, 2021)
Objective: For patients with symptomatic intracranial artery stenosis (sICAS), endovascular treatment is feasible and safe in recent studies. However, in-stent restenosis (ISR) predicts the recurrence of ischemic stroke. We attempt to elucidate the long-term risk factors for ISR from a multicenter trial of stenting for symptomatic intracranial artery stenosis registry in China. Methods: We retrospectively analyzed 97 patients with sICAS from a prospective registry trial that included 20 centers from September 2013 to January 2015. Cases were classified as the ISR group or non-ISR group. The baseline characteristics and long-term follow-up were compared between the two groups. Binary logistic regression analyses were identified as an association between ISR and endovascular technique factors. Results: According to whether ISR was detected by CT angiography, 97 patients were divided into the ISR group (n = 24) and the non-ISR group (n = 73). The admission baseline features and lesion angiography characteristics were similar, while plasma hs-CRP (mg/L) was higher in the ISR≥50% group at admission (8.2±11.4 vs 2.8±4.1, p=0.032). Binary logistic regression analysis identified shorter stents (adjusted OR 0.816, 95% CI 0.699 to 0.953; p=0.010), balloon-mounted stents (adjusted OR 5.748, 95% CI 1.533 to 21.546; p=0.009), and local anesthesia (adjusted OR 6.000, 95% CI 1.693 to 21.262; p=0.006) as predictors of ISR at the 1-year follow-up. Conclusions: Shorter stents, balloon-mounted stents implanted in the intracranial vertebral or basilar artery, and local anesthesia were significantly associated with in-stent restenosis. Further studies are required to identify accurate biomarkers or image markers associated with ISR in ICAS patients. Keywords: cerebrovascular disease, stroke, endovascular treatment, Interventional Neurology, intracranial in-stent restenosis